Replacement of soybean meal with guar meal in the diet of rainbow trout, Oncorhynchus mykiss (Walbaum 1792) : biological parameters and flesh quality - Esfandyar Najafi Hajivar (2021)
The present study investigated the effects of a diet containing guar meal, as a substitute for soybean, in rainbow trout Oncorhynchus mykiss (Walbaum 1792). The juvenile fish were fed with a soybean meal diet as basal diet and guar meal diets as substitute diets with replacement levels of 25, 50, 75 and 100 % (represented by 25PR, 50PR, 75PR and 100PR, respectively). Growth performance, feed utilisation, and body composition were investigated. Condition factor of fish fed 100PR was significantly lower than other treatments. Maximum and minimum survival of fish were observed in 50PR and 75PR treatments, respectively. Eviscerated fat of fish in 75PR and 100PR groups were significantly (P < 0.05) higher than other treatments. There was no significant difference in the other parameters between experimental treatments. The results indicate that there was no adverse effect in rainbow trout juveniles fed guar meal in the diet and thus could be an appropriate substitute for soybean meal in fish diet.